Triterpenes and phytosterols from Scaevola taccada collected in Ly Son island, Quang Ngai province, Vietnam - Phuong Thao, Tran Thi; Huyen, Pham Thi; Anh, Duong Van; Cam, Do Xuan; Anh, Nguyen The; Loc, Tran Van; Sung, Tran Van (Vietnam Journal of Chemistry, 2015)
From the ethyl acetate extract of the leaves of Scaevola taccada (Gaertn.) Roxb., two triterpenes (ursolic acid 6, myricadiol 5), two sterols (β-sitosterol 3, β-sitosterol glycoside 4), together with two long-chain hydrocarbons, tritriacontane 1 and tetracosane 2 have been isolated. Their structures were elucidated by the analysis of the IR, MS and NMR 1D and 2D spectra. Compound 1, 2, 3, 5, 6 were isolated for the first time from Scaevola taccada.